1983
DOI: 10.2337/diab.32.2.s47
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Enzyme Activities in Diabetes Mellitus in Relation to Endothelial Damage

Abstract: Increased platelet reactivity has been suggested in the pathogenesis of both arteriosclerosis and diabetic microangiopathy. Therefore, platelet function and platelet enzyme activities were assessed in a large group of 357 diabetics (256 patients with IDDM, aged 16-49 and 101 patients with NIDDM, aged 50-78) and 163 matched controls, and related to photographically documented retinopathy (Rd) and to peripheral vascular disease (PVD) as well as to plasma levels of von Willebrand factor (VIII R:Ag) as an indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…6). Plasma concentrations of von Willebrand factor protein are also closely correlated with ADP-induced platelet aggregation in vitro [98]. .…”
Section: Endothelial Cell Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…6). Plasma concentrations of von Willebrand factor protein are also closely correlated with ADP-induced platelet aggregation in vitro [98]. .…”
Section: Endothelial Cell Activationmentioning
confidence: 99%
“…Relative and absolute measures of regional myocardial blood flow can be obtained [111]. Positron emission tomography has been reported to detect coronary artery disease with a sensitivity of 92 % and a specificity of 89 % [98]. Preferably, resting myocardial perfusion scintigraphy is combined with exercise testing to unmask reduced myocardial blood flow reserve [111].…”
Section: Coronary Blood Flow Reservementioning
confidence: 99%
See 1 more Smart Citation
“…vWF is released when endothelial cells are damaged (16). vWF levels are higher in diabetic patients than in control subjects (18,(21)(22)(23), and the levels are even higher among diabetic patients with clinical nephropathy or retinopathy (17)(18)(19)(20)23). Qualitative abnormalities of vWF antigen and changes in the proportion of high-molecular weight multimers have also been reported in diabetes (17)(18)(19)(20)(21).…”
Section: Hemostatic Factor Levels and Hba 1cmentioning
confidence: 83%
“…Interestingly, a small study suggested that increased vWF was associated with the development of microalbuminuria in type 1 diabetes but not with the development of retinopathy (32). However, vWF levels have been reported to be higher in diabetic patients with retinopathy compared with control subjects or diabetic patients without retinopathy (19,23).…”
Section: Feng and Associatesmentioning
confidence: 99%